PECULIARITIES OF THE NUCLEOSINTHESIS OF HEAVY ELEMENTS IN A DISK OF SPIRAL GALAXY - Acharova, I. A.; Mishurov, Yu. N.; Lepine, J. R.D. (Одеські астрономічні публікації, 2008)
The goal of paper to see that different models for spiral pattern of galactic disks lead to distinguishable radial distribution of heavy elements. Moreover it will be explained why the distributions, demonstrated different chemical elements show different pattern. This fact has extremely importance for understanding of the processes, which occur in a galactic disk and allows to narrow down the possible class of their models.